DETECTION OF EXTENDED SPECTRUM BETA LACTAMASES IN ESCHERICHIA COLI ISOLATES - SAMEENA K; LAKSHMI K; CHITRALEKHA S; AISHWARYA JR (International Journal of Pharma and Bio Sciences, 2013)
Escherichia coli is known to cause various infections. The continued emergence of ESBLs in E.coli presents a great challenge to the practitioners in treating the infections. The aim of the study is to assess the prevalence of Extended-spectrum ß-lactamase (ESBL) producers among the E.coli isolates. Hundred isolates of E.coli from various samples were included in the study. All isolates were identified by standard conventional methods. Antibiotic sensitivity testing was done using disc diffusion technique by Kirby Bauer method and noted. Isolates with resistance or decreased susceptibility to third generation cephalosporins or aztreonam were selected as ESBL producers. ESBL production was detected by Double disk synergy test (DDST). 37% of the E.coli isolates were found to be ESBL producers. Most of the ESBL producing E.coli were found to be multidrug resistant. Hence, monitoring of ESBL production and antimicrobial susceptibility testing as a routine is necessary to prevent therapeutic failure and development of multidrug resistance among the bacterial isolates.